Case report: A Chinese patient with glutathione synthetase deficiency and a novel glutathione synthase mutation - Wu, Xiaojiao; Jiao, Jiancheng; Xia, Yaofang; Yan, Xiaotong; Liu, Zehao; Cao, Yanyan; Ma, Li (Frontiers in Pediatrics, 2023)
Glutathione synthetase deficiency (GSSD) is an autosomal-recessive metabolic disorder caused by glutathione synthetase (GSS) gene mutations. No more than 90 cases of GSSD have been reported worldwide; thus, the spectrum of GSS mutations and the genotype-phenotype association remain unclear. Here, we present a severely affected infant carrying a compound heterozygous GSS variation, c.491G>A, and a novel variant of c.1343_1348delTACTTC. We also summarize the clinical manifestations, treatment protocol, prognosis, and genetic characteristics of previously reported GSSD cases in China. In this case study, our patient presented with tachypnea, jaundice, intractable metabolic acidosis, and hemolytic anemia.Urinary-organic acid analysis revealed elevated 5-oxoproline levels. Further, this patient showed improved outcomes owing to early diagnosis and the timely administration of vitamins C and E. Therefore, our study indicates that in clinical cases of unexplained hemolytic anemia and metabolic acidosis, GSSD should be considered. Additionally, genetic testing and antioxidant application might help identify GSSD and improve the prognosis.